Healthcare professionals interpersonal variability and determinants of medical decision thresholds for active management of extremely preterm infants in a level 3 perinatal center in France - Charlotte Girard; Hélène Collinot; Héloïse Torchin; Clara Rollet; Pierre-Henri Jarreau; François Goffinet (PLoS ONE, 2025)
Background Before 26 weeks of gestational age, because extremely preterm infants (EPI) face a high risk of death or disability, management decisions may involve either active treatment or palliative care. Survival chances largely depend on the willingness of medical teams and parents to opt for active management. Variability of practices explains differences in survival between countries and regions, and interpersonal variability may also exist among caregivers within the same center. Our objective was to study the variability of management decisions and their determinants among caregivers in a French type 3 maternity hospital. Methods All caregivers, obstetricians, pediatricians, and midwives, involved in the management of EPI in a type 3 perinatal center were surveyed using a self-administered questionnaire. Each respondent reported their personal thresholds for deciding on active management, defined as the unborn child’s estimated likelihood of survival without severe neonatal morbidity. Median and interquartile ranges (IQR) of these thresholds were calculated and compared by respondent characteristics. Results 85 (75%) eligible professionals responded. The median threshold of survival without severe neonatal morbidity below which active management was deemed impossible was 15% (IQR 10-30%), while the median threshold above which active management could not be refused was 80% (IQR 70-90%). Wide IQRs indicated significant variability in individual thresholds. This variability appeared to be influenced by profession and gender but was not associated with factors such as having children, age, experience, or the personal estimates of the neonates’ outcomes. Conclusions Decision thresholds for active management of EPI, expressed in terms of survival without severe neonatal morbidity, vary significantly among professionals. The thresholds reported in our study were notably higher than those observed in other countries, which may help explain the lower rates of active management before 26 weeks in France. Recognizing these differences and comparing personal thresholds with peers could facilitate more consensus-based decision-making within teams.